2006
DOI: 10.1097/01.mlg.0000202091.34295.05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Navigation System for ENT with Surgical Efficiency Criteria

Abstract: The aim of this study is the evaluation of a navigation system (NaviBase) for ENT surgery. For this purpose, a new methodology for the evaluation of surgical and ergonomic system properties has been developed. The practicability of the evaluation instruments will be examined using the example of the overall assessment of the system in comparison with the current surgical standard and with other systems using clinical efficiency criteria. The evaluation is based on 102 ENT surgical applications; of these, 89 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 13 publications
(20 reference statements)
2
39
0
5
Order By: Relevance
“…With respect to this classification, image-guided navigation systems for minimally invasive surgery can be classified as a low to medium level of information automation, as these systems support to some degree the information acquisition and analysis of visual information from the operative site (i.e. they provide additional information needed to localize the position of the surgical instrument in relation to the patient's anatomy) while still leaving it completely up to the surgeon to draw any decisions from this information and to take any appropriate surgical action (13).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to this classification, image-guided navigation systems for minimally invasive surgery can be classified as a low to medium level of information automation, as these systems support to some degree the information acquisition and analysis of visual information from the operative site (i.e. they provide additional information needed to localize the position of the surgical instrument in relation to the patient's anatomy) while still leaving it completely up to the surgeon to draw any decisions from this information and to take any appropriate surgical action (13).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have not demonstrated similar benefits of IGS. [1217][1218][1219][1220] Strauss et al 1221 proposed a novel strategy for assessing the impact of IGS on surgical decision-making. In this clinical series, IGS was associated with changes in surgical technique and strategy, even for experienced surgeons.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 99%
“…En cuanto a sus ventajas la navegación permitiría realizar una planificación quirúrgica preoperatoria, ahorrar tiempo quirúrgico, una exploración más completa en un área potencialmente peligrosa manteniendo la indemnidad de estructuras nobles, favorecer la formación de futuros cirujanos y acortar su curva de aprendizaje, además de ser beneficiosa en la confirmación de la indemnidad quirúrgica de estructuras nobles en cirugía sinusal, especialmente en cirujanos menos experimentados 10 . Se espera que el error objetivo razonable esté en el rango de 1,5 a 2,0 mm con esta herramienta, utilizándose navegación con realidad aumentada se ha estimado un error de 1,5 mm o menos 11 , en un estudio reciente el uso de navegación virtual 3D no demostró superioridad en comparación a una guía de imagen triplana convencional 12 .…”
Section: Discussionunclassified